If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5 + -15) = m + -5 Combine like terms: 5 + -15 = -10 3(-10) = m + -5 Multiply 3 * -10 -30 = m + -5 Reorder the terms: -30 = -5 + m Solving -30 = -5 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -30 + -1m = -5 + m + -1m Combine like terms: m + -1m = 0 -30 + -1m = -5 + 0 -30 + -1m = -5 Add '30' to each side of the equation. -30 + 30 + -1m = -5 + 30 Combine like terms: -30 + 30 = 0 0 + -1m = -5 + 30 -1m = -5 + 30 Combine like terms: -5 + 30 = 25 -1m = 25 Divide each side by '-1'. m = -25 Simplifying m = -25
| 3x+25=12x+83 | | 3a-1(-1)=-5 | | 4(3y-3)-2y=-9 | | 4v+-3v-4=13 | | 6x^2-2x^3-4x=0 | | 2k-16-10k=-2k | | 207-7x=38x+22 | | -12-3+9= | | 6(x+4)-(2x-8)= | | 5-(-8)=x | | y^2-5y-3=0 | | 5(d-6)+6= | | 2m^3-5m^2-12m=0 | | (2x-3)+(x^2-4x)=180 | | 5x^2+3x-16=32-31x | | -3u+8=14 | | c-(-2)=68 | | 3y+4=-20 | | 56=4y | | 50=(x+10)x | | [(5*6-4)-20]= | | 2a+10=26 | | c+-52=68 | | x-9.51=2.4 | | -2b+8=-8 | | 241=5(5-7x)+8x | | 3c+5=-13 | | -5+(8-14)-(-4-9)= | | 17=3(p-4)+8 | | 10n-15=85 | | -2b+(-3)=7 | | -5.6+-15= |